2009
DOI: 10.1152/ajplung.90347.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells produce Wnt isoforms and TGF-β1 that mediate proliferation and procollagen expression by lung fibroblasts

Abstract: Studies have been carried out previously to determine whether mesenchymal stem cells (MSC) influence the progression of pulmonary fibrosis. Here, we asked whether MSC (derived from mouse bone marrow and human umbilical cord blood) produce factors that mediate lung fibroblast (LF) growth and matrix production. MSC-conditioned media (CM) were found by ELISA to contain significant amounts of PDGF-AA and transforming growth factor-beta1 (TGF-beta1). Proliferation was increased in a concentration-dependent manner i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 43 publications
4
95
5
2
Order By: Relevance
“…The associations between the Wnt pathway and MSCs (Salazar et al 2009) were further examined in the present study. We found that irradiation of nHLFs enhanced Wnt signaling, consistent with earlier reports (Gurung et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The associations between the Wnt pathway and MSCs (Salazar et al 2009) were further examined in the present study. We found that irradiation of nHLFs enhanced Wnt signaling, consistent with earlier reports (Gurung et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, co-culture systems have been used widely to investigate the effects of MSCs on other cell types. Although there is evidence that co-culture with MSCs promotes fibroblast proliferation (Kim et al 2007;Salazar et al 2009), information is lacking concerning the effects of MSCs on irradiated lung fibroblasts. Here, we found that co-culture with HUMSCs attenuated the radiation-induced up-regulation of α-SMA in nHLFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,36 However, MSCs potentiate fibrotic differentiation of other mesenchymal cells by secreting profibrotic mediators, such as TGF-␤1. 37 Thus, although MSCs can likely modulate an inflammatory microenvironment, they can also promote fibrogenesis by secreting profibrotic mediators 37 or differentiating to myofibroblasts. Regulation of native LR-MSC synthetic function and fibrotic differentiation fate by the local milieu might play a central role in dictating whether these cells serve a predominant immunoregulatory function or promote fibroproliferative events that favor the development of BO.…”
Section: Discussionmentioning
confidence: 99%